Perbedaan Tingkat Perilaku Prokrastinasi Akademik berdasarkan Jurusan Peserta Didik di SMK - Sri Fani Dayanti; Netrawati Netrawati; Yeni Karneli; Zadrian Ardi (PAKAR Pendidikan, 2023)
Learners are important members of academic institutions, where they are tasked with fulfilling their fullest potential and are consistently presented with scholarly and extracurricular obligations. It is expected that students have the ability to fulfill these academic tasks. However, students, in particular, show a tendency to procrastinate, resorting to copying homework from their peers, completing assignments during school hours, or submitting homework late with respect to other subjects. The purpose of this study is to determine the level of academic procrastination in each student major at SMKN. This study used quantitative research methodology with a descriptive approach. The research sample consisted of 192 students belonging to 7 classes and four majors. This study compares the differences in the level of students' academic procrastination behavior based on the majors taken through a questionnaire consisting of 34 closed statement items and five alternative answers. The results showed that the tendency of academic procrastination of each student major in SMKN was classified as moderate. This shows that academic procrastination behavior is still experienced by students in each department. In order for this academic procrastination behavior not to increase, follow-up is needed to overcome academic procrastination among students, such as using guidance and counseling services.